Опыт лечения инфицированного панкреонекроза - Воронов, А.Н. (Таврический медико-биологический вестник, 2010)
На когорті хворих (143 особи) на гострий панкреатит показано результативність використання октрестатину, що проявилося зниженням загального шпитального ліжко-дня, прискоренням редукції набряку підшлункової залози, попередженням хвилеподібного перебігу захворювання, покращенням якості життя згідно критерію зникнення болю. Октрестатин може бути рекомендованим як ефективний засіб зниження екзокринної функції підшлункової залози. The aim of the work was to determine the optimal surgical approach in patient with the different forms of infected necrotizing pancreatitis. The results of 59 patients treatment were analyzed. Patients were divided into 2 groups depending on the period of the disease and operation. The first group was formed from 27 patients, which were operated during the first and second phases of disease. The second group was formed from 32 patients, which were operated during the phase of infected complications. Mortality in the first group was 55,6%, in the second – 18,8%. The treatment of the infected necrotizing pancreatitis has to be strictly surgical. Success in infected necrotizing pancreatitis management depends on the completeness of inviable tissues removing.